Investigation of room temperature multi-functional properties of Nd doped mullite Bi2Fe4O9. (February 2020) - Krishna Rao, Subha; Meher Abhinav, E.; Jaison, D.; Sundararaj, Anuraj; Santhiya, M.; Althaf, R.; Gopalakrishnan, Chandrasekaran
Abstract: Mullite type Bi2 Fe4 O9 (BFO) and Nd doped Bi2 Fe4 O9 (BNFO) systems were developed using conventional solid state route under normal atmospheric pressure. The structural phase compositions were analyzed using x-ray diffraction (XRD). The analysis revealed BFO orthorhombic primary phase with traces of secondary phase and compressive lattice structural distortion, the same being evident from theoretically calculated (LSDA + U and PBE + U)correlated systems, where LSDA is Local spin density approximation, Hubbard U = 4.5eV and PBE is Perdew, Burke and Ernzerh of exchange correlation functional. Raman spectral analysis showed changes in the frequency and line width with respect to Nd doping, which correlates the lattice distortion observed in XRD analysis. Henceforth, the Bi2-x Nd2x Fe4 O9 with x = 0, 0.01, 0.03, will be referred as BFO, BNFO1 and BNFO3. From the dielectric and optical studies, a significant increase in the dielectric constant and narrower band gap was observed in the BNFO samples, compared to BFO. The room temperature vibrating sample magnetometer (VSM) analysis of the BNFO samples showed weak ferromagnetic hysteresis behavior. Also, a significant enhancement of magnetic moment was observed with increased concentration of Nd in BNFO samples. This could be due to suppression of oxygen vacancies by the Nd dopant, that reduces the super-exchange interaction of Fe 3+ -O-Fe 3+ and introduce Dzyaloshinskii-Moriya (D-M) interactions. The BNFO3 with control over its dielectric constant, optical band gap and magnetization by doping, makes it a viable material for magneto-electric and other multifunctional applications. Graphical abstract: Image 1 Highlights: Bi2 Fe4 O9 exhibits enhanced multifunctional properties on doping with Neodymium. XRD analysis shows that the unit cell volume reduced with increased Nd doping which lead to decrease in particle size. Bi2 Fe4 O9 doped with Neodymium – enhanced ferromagnetic behavior at room temperature. Narrow band gap observed for 3% Nd doped BFO (BNFO3), suggests an improved electrical conduction. Dielectric constant and dielectric loss was high for BNFO3.